Crystal Structure of the YgfZ Protein from Escherichia coli Suggests a Folate-Dependent Regulatory Role in One-Carbon Metabolism - Teplyakov, Alexey (J Bacteriol, 2004)
The ygfZ gene product of Escherichia coli represents a large protein family conserved in bacteria to eukaryotes. The members of this family are uncharacterized proteins with marginal sequence similarity to the T-protein (aminomethyltransferase) of the glycine cleavage system. To assist with the functional assignment of the YgfZ family, the crystal structure of the E. coli protein was determined by multiwavelength anomalous diffraction. The protein molecule has a three-domain architecture with a central hydrophobic channel. The structure is very similar to that of bacterial dimethylglycine oxidase, an enzyme of the glycine betaine pathway and a homolog of the T-protein. Based on structural superposition, a folate-binding site was identified in the central channel of YgfZ, and the ability of YgfZ to bind folate derivatives was confirmed experimentally. However, in contrast to dimethylglycine oxidase and T-protein, the YgfZ family lacks amino acid conservation at the folate site, which implies that YgfZ is not an aminomethyltransferase but is likely a folate-dependent regulatory protein involved in one-carbon metabolism.